IMPLIKASI POLA ASUH STRAWBERRY GENERATION TERHADAP PENDIDIKAN KARAKTER ANAK MENURUT PERSPEKTIF ISLAM - Haris, Abdul (INTEGRATIF |Jurnal Magister Pendidikan Agama Islam, 2024)
The purpose of this study is to analyze the problems related to parenting patterns of parents towards children, which make them a strawberry generation or strawberry generation and its implications for children's character according to an Islamic perspective. Then provide solutions with Islamic educational values and parenting patterns or methods of educating children in Islam so that children have good character or morals, are tough and become a reliable next generation. This research uses a qualitative approach with descriptive methods and data collection techniques of literature and document studies. The results of this study reveal that the phenomenon of character crisis in the strawberry generation era occurs because of the wrong parenting patterns and character education at home is not carried out properly and correctly. The process of character education in Islam towards children can be through several ways, namely through exemplary, habituation, wise advice, attention and supervision and punishment.